Enhancing Grade 11 Students’ Academic Performance in Statistics and Probability Through Magnified Math Solutions Strategy: A Classroom-Based Action Research (Statistics and Probability) - Nuera, Emmanuel Moñez (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The poor academic performance in Statistics and Probability has been one of the significant challenges in teaching and learning during the COVID-19 pandemic, especially under modular distance learning. This action research aimed to improve the academic performance of Grade 11 TVL ICT-CSS learners at Kinan-oan High School, Trinidad II District, through the Magnified Math Solutions Strategy during School Year 2021–2022. The strategy was designed to enhance learners’ metacognitive skills by using a Learning Progress-Inquiry Form to gather self-assessments and specific learning inquiries. These inputs guided the creation of detailed math solutions and differentiated supplementary activities tailored to students' individual learning needs. Twenty-seven (27) learners participated in the study. A comparative analysis of their academic performance before and after the intervention revealed an improvement: learners classified as Fairly Satisfactory decreased from eleven (11) to three (3). The mean academic performance increased from 81.70% to 86.26%, showing a 4.56% gain. A paired sample t-test yielded a t-statistic of 37.54 and a p-value of < .001, indicating a statistically significant difference in learners’ performance before and after the intervention. The findings suggest that the Magnified Math Solutions Strategy is effective in improving academic performance in Statistics and Probability by promoting metacognition, differentiated instruction, and self-directed learning. However, since the study was conducted during modular distance learning with a small sample size, further research is recommended to validate its effectiveness in face-to-face settings and across more diverse learner populations.